Le nostre coincidenze - Palumbo, Matteo (Status Quaestionis, 2013)
How can we narrate coincidences? What are the ways and techniques to make them work in the narrative world? What are their characteristics with respect to providence’s great ideological and narrative mechanism? Is there a difference between their function in narrative and in lyric poetry? Does the poetics of coincidences change during modernity? The typology outlined in this introductory essay hybridizes the essential semantics of the notion with various theoretical stances; while doing so, it draws on various examples ranging from canonical Italian authors (e.g. Manzoni and Leopardi) to film directors – such as David Lynch – who especially tackled the issue and made it play a pivotal role in their works.